Cytotoxicity Studies of Mortierella alpina AIB RR2 Extracts on Hela and a549 Cell Lines - Mishra, Raghvendra Kumar (Asian Journal of Pharmaceutics (AJP), 2018)
Aim: The aim is to understand any possible cytotoxic activity of Mortierella alpina extract against carcinoma cell lines and possible interaction with normal cell lines. Materials and Methods: The extract of M. alpina at varying concentrations was incubated with the normal Vero cell lines and also the carcinoma cell lines HeLa and A549, after which 3-[4,5-dimethylthiazol-2-yl]-2,5 diphenyl tetrazolium bromide assay was carried out to determine the viable cell. Results and Discussion: The cytotoxic activities of M. alpina extract were quite strong against both HeLa and A549 carcinoma cell lines with inhibitory concentration 50 values of 106 and 116 Î¼g/mL, respectively. However, the cytotoxic concentration 50 value of the fungal extract against the normal Vero cell line was 2674 Î¼g/mL, which shows the very low toxic activity of the fungal extract against the normal cell lines. Further, the therapeutic index of M. alpina against HeLa and A549 cell lines was found to be 25.22 and 23.02, respectively. Conclusion: The present investigation indicates the probable use of M. alpina extracts in the treatment of carcinoma.